Screening for retinopathy, risk factors, adherence to treatment and complications among diabetic and hypertensive individuals attending a primary care centre in Puducherry, India - Hansdak, Amod; V., Saravanan; ., Manikandan; ., Navin; Bazroy, Joy; ., Velavan; Purty, Anil J. (International Journal of Research in Medical Sciences, 2018)
Background: The increasing prevalence and incidence of diabetes and hypertension with increasing age and adult age group are at high risk of developing diabetic and hypertensive retinopathies. Methods: The study was conducted in a rural area of Puducherry, data collection was carried over a period of six months. Self-reported patients of diabetes and hypertension were included in the study and predesigned questionnaire was used to collect the information about socio-demographic details, risk factors, physical activity, history related to DM/HTN and history of fundus examination. Results: Majority of patients screened for diabetes 56% and hypertension 47% was by government hospital. The proportion of diabetics and hypertensives who had undergone fundus examination to rule out diabetic and hypertensive retinopathy was found to be 29.3% (12) and 14.5% (10). Complications such as neuropathy and retinopathy were given by 36.5% (15) and 2.4% (1) of diabetic patients Two third of the patients 64.1% had sedentary life style. Conclusions: Health care providers need to plan for larger coverage of fundus examination among diabetic and hypertensive patients.